2019
DOI: 10.31230/osf.io/zgupd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The shifting distribution of Mediterranean fishes: a spatio-temporal assessment based on Local Ecological Knowledge .

Abstract: A major problem worldwide is the rapid change in species abundance and distribution, which is rapidly restructuring the biological communities of many ecosystems under changing climates. Tracking these transformations in the marine environment is crucial but our understanding is often hampered by the absence of historical data and by the practical challenge of survey large geographical areas. Here we focus on the Mediterranean Sea, a region which is warming faster than the rest of the global ocean, tracing bac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…This study has shown that LEK can be useful for collecting behavioural and ecological information on elasmobranch populations. LEK has already proven to be important for studying abundance trends of commercially exploited elasmobranchs in GSA 16 (Colloca et al, 2020) as well as several aspects of other marine species (Azzurro et al, 2011(Azzurro et al, , 2019Maynou et al, 2011), but this is the first time that the study of elasmobranch behaviour has been applied in Mediterranean GSAs collectively. As a general perspective on LEK-based information, the robustness of the data collected from fishers was supported by their long average fishing experience and by the fact that many fishers did not change fishing areas during their activity, and if changed, the new fishing areas were within the same GSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has shown that LEK can be useful for collecting behavioural and ecological information on elasmobranch populations. LEK has already proven to be important for studying abundance trends of commercially exploited elasmobranchs in GSA 16 (Colloca et al, 2020) as well as several aspects of other marine species (Azzurro et al, 2011(Azzurro et al, , 2019Maynou et al, 2011), but this is the first time that the study of elasmobranch behaviour has been applied in Mediterranean GSAs collectively. As a general perspective on LEK-based information, the robustness of the data collected from fishers was supported by their long average fishing experience and by the fact that many fishers did not change fishing areas during their activity, and if changed, the new fishing areas were within the same GSA.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from previously available studies (see, for instance, Azzurro et al, 2011Azzurro et al, , 2019Maynou et al, 2011), a semistructured questionnaire was developed and translated into different languages. The questionnaire response collection was carried out by trained marine biologists assisted with species tables to allow accurate taxonomic identification by fishers.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, many species that were previously confined to the South are now expanding their geographical distribution northwards, a phenomenon also addressed to as "meridionalization" (Riera et al 1995, Azzurro 2008, Azzurro et al 2011, Bianchi et al 2018). These species include thermophilic fish such as the bluefish (Pomatomus saltatrix), the yellowmouth barracuda (Sphyraena viridensis), the grey triggerfish (Balistes capriscus), the common dolphinfish (Coryphaena hippurus) and the Mediterranean parrotfish (Sparisoma cretense), which are increasingly observed at higher latitudes than those in their native geographical distribution (Dulčić 1999, Dulčić and Pallaoro 2001, Dulčić and Soldo 2004, Bianchi 2007, Azzurro et al 2011, Bianchi et al 2012, Villegas-Hernández et al 2015, Bianchi et al 2018, Azzurro et al 2019. Nevertheless, there is limited knowledge about the specific local dynamics acting at the different mediterranean subregional levels.…”
Section: Introductionmentioning
confidence: 99%
“…Local Ecological Knowledge (LEK), defined as the cumulative body of knowledge (practice and beliefs) of individuals during their lifetimes (Berkes et al 2000, Gilchrist et al 2005, has been long recognized as a tool for environmental monitoring and natural resources management (Berkes et al 2000, Sagarin andPauchard 2010). LEK can be used for sampling the quantitative abundance of wild population with the advantage of being cheap, feasible and extremely useful to complement traditional sampling surveys (Anadón et al 2009, Azzurro et al 2011, Coll et al 2014, Azzurro et al 2018, also on the large geographical scale (Azzurro et al 2019).…”
Section: Introductionmentioning
confidence: 99%